Development of arm-type launching machine for badminton - Sakai, S.; Shirayama, H. (Transactions of the JSME, 2015)
Badminton shuttlecock has a complicated shape consisting of 16 goose feathers from a waterfowl and a hemispherical cork. Also, the specific air resistance of the shuttlecock is large and its mass is lightweight, weighing approximately 5.2 g. When the shuttlecock is hit with a racket or launched by a machine at speeds higher than an initial velocity of 30 m/s, the feather parts of the shuttlecock are typically damaged or broken by large impulse load. In this study, a badminton launching machine using a revolving launch arm has been developed with a new launcher mechanism that can discharge at high speeds to reduce the damage to the shuttlecock feathers. The launcher mechanism of the shuttlecock was rotated at a high speed from the launch arm, which held the shuttlecock with a grip tool at the end of the arm rod. The results of the launching experiments using the arm-type badminton machine show that the machine can project the shuttlecock the highest at initial speeds of 36.0 m/s, with a maximum flight distance of approximately 9.2 m and the standard deviation of the shot and lateral directions of 0.30 m and 0.17 m, respectively. In addition, the dimension and the shape of the grip tool with the shuttlecock were examined to determine their influence on the launching performance of the badminton machine.